A parallel computing approach for integrated security assessment of power system. (June 2016) - Varshney, Sarika; Srivastava, Laxmi; Pandit, Manjaree
Highlights: Parallel computing environment is developed for integrated security assessment. The method utilizes full AC load flow and continuation load flow programs. Sparsity technique is used in the LF and in CPF programs. Parallel computing has been proposed using PCT software. Approach is demonstrated on IEEE 30-bus and NREB 246-bus Indian power. Abstract: Fast and accurate assessment of integrated security of present day complex and highly interconnected power system within time frame is a challenging task. The traditional methods used for integrated security assessment are fast but approximate. On the other hand, full simulation methods provide more accurate security assessment, but require large computation time. This paper proposes the use of parallel computing for fast and accurate assessment of integrated security of power system by running full Newton Raphson (NR) load flow program with sparsity technique to compute real power flow or MW performance index ( MWPI ), and voltage performance index ( VPI ), and continuation power flow program with sparsity technique to compute voltage stability index ( VSI ) for all possible single line outage contingencies. The proposed work has been carried out using the Matlab Parallel Computing Toolbox Software (PCTS). To implement parallel computing, the job scheduler, a part of PCTS, divides a computationally intensive job into various tasks and distributes these tasks to its assigned workers for evaluation. Effectiveness of the proposed approach has been demonstrated on IEEE 30-bus system and a practical NREB 246-bus Indian power system. As the proposed method utilizes NR load flow and continuation load flow programs, the accurate post contingency operating status of a power system is also available, which can be used for appropriate corrective actions planning to bring the power system back into secure state. The proposed approach is quite accurate and fast and hence can be implemented for integrated security assessment of practical power systems in smart grid environment also.